Esthetic strategy in the novels «Dreamer» by Ivan Navumenka and «Stone out of the mountain» by Uladzimir Damashevich - Novoseltseva, Ganna V. (Journal of the Belarusian State University. Philology, 2019)
The main first-person narrative strategy lets Ivan Navumenka and Uladzimir Damashevich create the psychological portrait of an artistic person, think of the problem in connection with social surroundings, pay attention to living environment. In the novels «Dreamer» and «Stone out of the Mountain» the main characters are united by inner sensibility and social responsibility. The writer’s task is to show everyday life thorough characters’ feelings. This fact determines the content novel form: new problems appear, a simple person is in the center of philosophical analysis, the role of artistic details increases. The local writing tendency develops in the novel genre, romantic novel becomes more relevant.
Keywords: novel; romantic novel; esthetic strategy; main character; person; Ivan Navumenka; Uladzimir Damashevich